Literasi Berkelanjutan: Sinergi Mahasiswa dan Perpustakaan Nasional Membentuk Budaya Baca di Desa Mareje Lembar, Lombok Barat - Listantia, Nora; Nugraha, Lalu Muh. Lutfi; Toyyibah, Muliani Wardatun; Azizah, Nurlita; Ilmi, Nurul; Suryadi, Lalu Fahril Dwi; Nabila, Vira Lingga; Ramdhania, Atika; Azira, Intan; Abdillah, Yandika Fatwa; Jenadi, Lalu Anggiar (Jurnal Pengabdian Inovasi Masyarakat Indonesia, 2025)
Mareje Village is located in Lembar District, West Lombok Regency. It is known for its natural beauty, encompassing several tourist attractions, and for its distinctive character, surrounded by vast expanses of rice fields. Despite its immense potential, the village faces challenges in developing a culture of reading and literacy among its residents. To address this challenge, the Community Service Program (KKN-PMD) aims to increase reading and literacy among the Mareje community through various approaches and innovations. The KKN-PMD program emphasizes building a strong literacy foundation, contributing to human resource development and improving the community’s quality of life. Through the development of a community-based library, the provision of quality reading materials, and literacy training, it is hoped that the Mareje community will have good access to information and knowledge. This activity is also expected to encourage a high level of reading interest among various groups, strengthen literacy skills, and create an environment that supports continuous learning. The KKN-PMD program will be implemented for seven weeks, starting from July 8 to August 21, 2025, with the involvement of students and library management as the main facilitators, as well as active participation from the Mareje Village community in every activity with a total of 288 effective student working hours (JKEM). Overall, this KKN-PMD work program not only aims to increase the love of reading in Mareje Village, but also to create collective awareness of the importance of literacy in building a smarter and more competitive community. With collaboration between students and the community, Mareje Village can become a successful example in developing a sustainable reading culture.